Impact of Demographics and Insurance Coverage on Schizophrenia Treatment and Healthcare Resource Utilization Within an Integrated Healthcare System - Seo S; Healey BE; McLin R; Sacks NC; Benson CJ; Citrome L (Neuropsychiatric Disease and Treatment, 2024)
Sanghyuk Seo,1 Bridget E Healey,2 Ronae McLin,2 Naomi C Sacks,2 Carmela J Benson,1 Leslie Citrome3 1Medical Affairs Neuroscience, Janssen Scientific Affairs, LLC, a Johnson & Johnson company, Titusville, NJ, USA; 2PRECISIONheor, Boston, MA, USA; 3Department of Psychiatry and Behavioral Sciences, New York Medical College, Valhalla, NY, USACorrespondence: Carmela J Benson, Medical Affairs Neuroscience, Johnson & Johnson Innovative Medicine, 1125 Trenton Harbourton Road, Titusville, NJ, 08560, USA, Email Cbenson5@its.jnj.comPurpose: Little is known about the impact of health disparities on antipsychotic treatment and healthcare resource utilization (HRU) among patients with schizophrenia. The objective of this analysis is to examine treatment patterns and HRU by age, race/ethnicity, and insurance coverage among patients with schizophrenia in an integrated delivery network (IDN).Patients and Methods: This cross-sectional study used electronic health record data from MedStar Health, an IDN in the Baltimore-Washington, DC, area. Patients were aged ≥ 18 years and had ≥ 2 outpatient encounters or ≥ 1 hospitalization with a diagnosis of schizophrenia between January 1, 2017 and March 31, 2021. Outcomes assessed included oral antipsychotic prescriptions, long-acting injectable antipsychotic (LAI) utilization, hospitalizations, emergency department (ED) visits, and outpatient visits. Analyses compared subgroups based on age, race/ethnicity (non-Hispanic Black, non-Hispanic White, and other), and type of insurance coverage at index (Medicare, Medicaid, and other) during 12 months of follow-up.Results: A total of 78.1% of patients had ≥ 1 prescription for an antipsychotic and 69.1% received ≥ 1 second-generation antipsychotic. Second-generation long-acting injectables (SGA LAI) were utilized by 9.0% of patients, with the elderly and Medicaid beneficiaries having the lowest SGA LAI utilization. Overall, 61.7% of patients had ≥ 1 hospitalization, 56.4% had ≥ 1 outpatient visit, and 50.5% had ≥ 1 ED visit. Hospitalizations and ED visits were most common in those 18 to 24 years of age and in Medicaid beneficiaries, whereas outpatient visits were more common for the elderly and Medicare beneficiaries.Conclusion: At the population level, the results indicate widespread underprescription/underutilization of antipsychotics that have been shown to improve clinical and economic outcomes in patients with schizophrenia, particularly SGA LAI. Within specific subpopulations, disparities in treatment selection and HRU were observed, suggesting the need for increased attention to at-risk groups to ensure consistent quality of care regardless of age, race/ethnicity, or insurance coverage.Keywords: health disparities, race/ethnicity, antipsychotic prescription, long-acting injectable antipsychotics, second-generation antipsychotic, clinical outcomes